Identifying joint association between body fat distribution with high blood pressure among 7 ∼ 17 years using the BKMR model: findings from a cross-sectional study in China - Manman Chen; Xijie Wang; Yanhui Li; Di Gao; Ying Ma; Tao Ma; Yi Zhang; Li Chen; Jieyu Liu; Qi Ma; Mengjie Cui; Xinxin Wang; et al. (BMC Public Health)
Abstract Background To investigate the joint associations between various body fat distribution parameters and high blood pressure (HBP) using the Bayesian Kernel Machine Regression (BKMR) model in school-aged children. Methods A diverse sample of 7 ∼ 17 years old (N = 1423; 50.25% boys) was recruited for this study. Fat distribution parameters for multiple body parts, including trunk, legs, android region, and gynoid region fat percentage were measured. HBP was defined as either systolic or diastolic blood pressure exceeded age-, sex- and height-specific 95th percentiles. The chi-square test was utilized to compare differences between groups. The BKMR model was employed to analyze the joint effects of body fat indicators on HBP while accounting for potential confounders. Weighted Quantile Sum (WQS) model was used to characterize the relative weights of each body fat distribution parameter for HBP. Additionally, stratified analyses were performed by sexes and overweight/non overweight groups. Results HBP prevalence was 46.86% and 35.10% for overweight and obese (OB) boys and girls, and was 17.96% and 17.28% for non-overweight and obese (non-OB) boys and girls, respectively. Increased fat percentages of trunk, android, and gynoid parts are associated with a higher risk of HBP, while increased fat percentage of the leg was associated with lower HBP risk. Android fat percentage contributed the most HBP risk in OB boys (weight = 0.34), OB girls (weight = 0.39), and non-OB girls (weight = 0.56). Leg fat percentage had significant protective effect on HBP for non-OB boys (weight=-0.22) and OB boys (weight=-0.44), while gynoid fat percentage had significant protective effect for OB girls (weight=-0.27). Conclusions Fat distribution of various body parts have inconsistent roles and directions in their association with HBP risk in children of different sex and weight status. We recommend that children of different sexes and weight statuses be provided with body-part-specific exercise recommendations for optimal chronic disease prevention and control benefits.